Used of the light attractor in traps for catches in Bengkunat Waters, Pesisir Barat Regency - Aprilia Syah Putri Putri; Rama Agus Mulyadi; Denta Tirtana; Ayang Armelita Rosalia; Roma Yuli Hutapea (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2024)
Pesisir Barat is one of the locations that has a great opportunity for capture fisheries activities in Lampung. Bubu is a passive fishing gear, made of thick steel frames, woven nets with small openings. Bubu is usually used to catch fish or other small crustaceans, by luring them to swim and trapping them inside. In this study, we used a light attractor as bait. Thus, increasing the effect of the trap. It exploits the phototactic behavior exhibited by many fish species, which are attracted by light itself, or preys on light-attracted phototactic invertebrates. In this study we used two kinds of traps. First, those with light attractors, then those without light attractors. The purpose of this study was to determine the composition of the catch and comparing the result of both traps. This research was carried out from June to July 2022 with an estimated water depth of ±4-6 meters. The trap size is 120 cm x 70 cm x 80 cm. The composition of the catch on trap fishing gear consisted of several types of catch including blue-spotted grouper, red snapper, kuniran, baronang, cuttlefish, shrimp, squid and octopus. The result are quite different. The traps with LEDs having more result compared to traps without LED modifications.